Tuning of Surface Charge of Functionalized Poly(Carboxybetaine) Brushes Can Significantly Improve Label‐Free Biosensing in Complex Media (Adv. Mater. Interfaces 33/2022) - Víšová, Ivana; Houska, Milan; Spasovová, Monika; Forinová, Michala; Pilipenco, Alina; Mezuláníková, Kateřina; Tomandlová, Markéta; Mrkvová, Kateřina; Vrabcová, Markéta; Dejneka, Alexandr; Dostálek, Jakub; Vaisocherová‐Lísalová, Hana (Advanced materials interfaces, 2022)
Poly(carboxybetaine) Functionalization Proper restoration of zwitterionic balance after functionalization of poly(carboxybetaine) brushes (pCB) is critical for pCB‐biorecognition coatings with excellent antifouling properties. In article number 2201210, Ivana Víšová, Milan Houska, Hana Vaisocherová‐Lísalová, and colleagues present a method using tailor‐made mixtures of agents allowing tuning of the surface charge balance. This approach improves antifouling of functionalized pCBs by several orders of magnitude, which has a significant impact on label‐free biosensing in complex media.